Critical point measurement of some polycyclic aromatic hydrocarbons. (January 2015) - Nikitin, Eugene D.; Popov, Alexander P.
Highlights: Critical properties of five polycyclic aromatic hydrocarbons were measured. These hydrocarbons decompose at near-critical temperatures. Pulse-heating method with short residence times was used. Abstract: The critical temperatures and the critical pressures of five polycyclic aromatic compounds, namely, acenaphthene, fluorene, anthracene, phenanthrene, and pyrene have been measured. All the compounds studied decompose at near-critical temperatures. A pulse-heating technique applicable to measuring the critical properties of thermally unstable compounds has been used. The times from the beginning of a heating pulse to the moment of reaching the critical temperature were from (0.06 to 0.85) ms. The short residence times provide little degradation of the substances in the course of the experiments. The experimental critical parameters of the polycyclic aromatic compounds have been compared with those estimated by five predictive methods. The acentric factors of polycyclic aromatic compounds studied have been calculated.